A First Study on Three HBB Gene Intronic SNPs: Molecular Profiling of β-Thalassemia Major in Southern Iraq - Mandal, Amar Mousa; Mahmood, Aseel Shakir (Iraqi Journal of Science, 2026)
Genetic association between HBB genetic variations and β-thalassemia is the key factor for management and counseling β-thalassemia. This innovative investigation aims to explore the connection between three intronic SNPs in the HBB gene rs7946748 (64G>A), rs7480526 (71A>C), and rs1451581925 (386A>T) and clinical outcomes in β-thalassemia major patients from Southern Iraq. Using PCR amplification and Sanger sequencing, 100 participants (50 patients and 50 controls) were analyzed. The study revealed a strong correlation between the AA genotype and the A allele of rs7480526 and a heightened risk for β-thalassemia and notable alterations in hematological parameters. Furthermore, rs7946748 and rs1451581925 were linked to increased ferritin levels and elevated liver enzyme markers, indicating iron overload and hepatic stress in transfusion-dependent cases. Linkage disequilibrium (LD) analysis demonstrated significant associations between the GAT and AAT haplotypes, as well as disease susceptibility. In conclusion, the findings indicate AA (OR 2.53;95%cl 1.12-5.70, and p value= 0.4*) genotype and A allele (OR 2.09:95% Cl 1.17-3.71 and p value = >0.01**) of rs7480526, along with haplotype analysis reveal co-inheritance patterns that deepen understanding of genotype-phenotype relationships and disease susceptibility.